Semiliberdade: monitorar, controlar e punir: engendrando os novos fluxos de controle - Taborda, Fabiane (2015)
This objective study to reflect on institutional functioning of the semi-liberty, its limits and its possibilities, as from the problematization of the data of this case in a study involving the national data and the analysis of the current socio-educational proposal. Semi-liberty is a juridical term used to appoint a modality of socio-educational measure of adolescent responsibility for their infractions, according to the brazilian Statute of Children and Adolescents (ECA Estatuto da Criança e do Adolescente) from 1990. This measure, according to the current legislation, consists in adolescent permanence in a house during a period from 6 months to 3 years, under the supervision and monitoring of a professional team with compulsory schooling and professionalization. One of the questions in this process is the relation between the functioning of the measure from its institutional (structure and organization) and intersectoral (organization and articulation with other public policies) strategies and the results of those actions in the life of these adolescents. Therefore, it was proposed to investigate the performance of institutional and intersectoral processes adopted by the semi-liberty socio-educational measurement developed in Foz do Iguassu, in the state of Paraná, focusing on institutional arrangements, behaviors, objectives of political actors, in the action tools and the institutional and intersectoral policy strategies. Starting from a qualitative, exploratory study, it was sought to perform pertinent questionings to the disciplinary power and to the society of control, respectively problematized by Michel Foucault and Gilles Deleuze. The theoretical discussion was coordinated with the experiences testified by the researcher and those reported by professionals of the House of Semi-liberty of Foz do Iguassu, in Paraná, added to the analysis of documents containing information about the socio-educational process of the attended adolescents and its consequences. The analysis of these experiences aimed to understand the existence of the object, its functioning correlated with the historical movement, a view not merely textual, but relational, discursive, in order to preserve the social unity and establish relations among the content - which appears -, the rules and the delimitations. The experiences and the objective data found on the functioning of semi-liberty indicate the transition movement of strategies interconnected to the control, disciplinary society according Foucault (2012f) and Deleuze (2010). The research focuses on the institutional and intersectoral strategies that combine the new to the old public policy model in the area of childhood and adolescence, interconnecting practices and political conceptions of the Children's Code to the Statute of Children and Adolescents . Practices in favor of the subject of universal law , that does not leave the idea of a dangerous subject on the job with the adolescent who commits an infraction. And, in this context, becomes a laboratory building new power relations, controlling and watching these adolescents to the model of life proposed by the democratic, participatory and inclusive society.